2009
DOI: 10.1097/tp.0b013e3181a664f1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Prolong Composite Tissue Allotransplant Survival in a Swine Model

Abstract: These results suggested that the regulatory activity of MSCs on T cells and GVHD might contribute to significant prolongation of composite tissue allotransplant survival in the MSC-BMT-CsA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 31 publications
2
77
0
Order By: Relevance
“…Bone marrow stromal cells (BMSCs) have recently been shown to suppress harmful immune responses in patients with acute graftversus-host disease (4,5) and in several animal models of allogeneic rejection (6)(7)(8), a variety of autoimmune diseases (9)(10)(11), and lung injury (12)(13)(14)(15). The authors of many of these studies concluded that BMSC-driven immunosuppression results from a shift in Th1/Th2 balance (8,16,17).…”
mentioning
confidence: 99%
“…Bone marrow stromal cells (BMSCs) have recently been shown to suppress harmful immune responses in patients with acute graftversus-host disease (4,5) and in several animal models of allogeneic rejection (6)(7)(8), a variety of autoimmune diseases (9)(10)(11), and lung injury (12)(13)(14)(15). The authors of many of these studies concluded that BMSC-driven immunosuppression results from a shift in Th1/Th2 balance (8,16,17).…”
mentioning
confidence: 99%
“…Based on previous observations, we speculated that BMSCs might represent a useful cell in clinical practices (Hu et al, 2010;Griffin et al, 2011;Gurudutta et al, 2012). Indeed, the advantage of employing large animals, such as pigs, rather than small animal models, is based on several factors, including disease complexity, effective cell dosage, cell survival after transplantation, as well as tissue related inflammatory and immunological responses to engraftment after transplantation (Poncelet et al, 2007;Kuo et al, 2009). Xiaomeishan porcine BMSCs were chosen for this study based on their similarity to human cells.…”
Section: Discussionmentioning
confidence: 99%
“…Among many available sources, mesenchymal stem cells (MSCs) derived from bone marrow or adipose tissue are commonly used as multipotent autologous cell sources and can be collected through relatively noninvasive methods. 1 A number of studies have demonstrated the advantages of using MSCs for the repair or regeneration of multiple tissue types, [2][3][4][5][6][7][8][9] and multiple clinical trials are underway investigating the use of MSCs for the treatment of both acute and chronic conditions. 10 Despite many studies establishing the benefits of MSCs, a number of factors remain unaddressed regarding their widespread use.…”
Section: Introductionmentioning
confidence: 99%